A simple proof of the brouwer fixed point theorem - S. Dhompongsa (2018)
© 2015 by the Mathematical Association of Thailand. All rights reserved. We give a new proof of the Brouwer fixed point theorem which is more elementary than all known ones. The only tool we use is the Tietze (continuous) extension theorem. The idea of the proof suggests some successful computation of a fixed point.